Chemical Preliminary Evaluation of leaves, Peels, and Fleshs Fruit of Limau Kuit: Local Orange of South Kalimantan - Azidi Irwan; Kamilia Mustikasari; Dahlena Ariyani (Jurnal Sains dan Terapan Kimia, 2017)
This research was conducted to know about fruit of limau kuit from South Kalimantan which includes weight, diemeter of fruit, volume of fruit juice, water content, and ash content of its flesh as well as water and ash content on leaves and fruit peel. Chemical preliminary examination includes measurement of pH of fruits juice and phytochemical screening test on leaves, fruit peel, and fruit flesh. The result is obtained with mean value as follows: weight 154,82 g, diameter of fruit 68,45 mm, volume of juice water 44,60 ml, water content of fruit flesh 67,16%, water content of fruit peel 65,67%, leaf water content 65,88%, ash content 0,72%, fruit ash content 1,39%, and leaf ash content 3,32%. Measurement of pH of fruit juice without dilution; 100x; 1000x; and 10000x dilutions showing a value of 1.62; 2.08; 2.68; and 3.33, respectively. The results of the phytochemical examination on fresh samples of leaves, fruit peels, and fruit juices showed all samples giving positive (+) test results against alkaloids, saponins, steroids, triterpenoids (except negative (-) for fruit skin samples), tannins, and flavonoids (except (-) for the juice of the fruit). While the samples with the fresh-dried treatment extracted each using ethanol and n-hexane solvents showed (+) results for all sample extracts in both fresh-dried treatments, except (-) saponins in dried leaves (ethanol extract) and fruit peels fresh (n-hexane extract). Tannin test for fresh leaf (n-hexane) and flavonoid for fresh leaves (ethanol extract) and fresh fruit peel (ethanol extract) showed negative results.Keywords: Limau kuit, South Kalimantan, chemical preliminary test, phytochemical test, ethanol extract, n-hexane extract.